Modernization of Pesantren: The Actualization and Relevance of the Thoughts of Maulana Syaikh TGKH. Muhammad Zainuddin Abdul Madjid in the Era of Society 5.0 - Husnul Haetami; Lubna Lubna; Moh. Iwan Fitriani (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2025)
This study examines the modernization of Islamic boarding schools (pesantren) through the actualization and relevance of the educational thought of Maulana Syaikh TGKH. Muhammad Zainuddin Abdul Madjid in the era of Society 5.0. Amid rapid technological advancement and shifting social dynamics, the study aims to analyze how Maulana Syaikh’s philosophy-rooted in spiritual intelligence (al-aql al-ruhani), moral leadership (al-qiyadah al-akhlaqiyyah), and social transformation (al-taghyir al-ijtima'i)-can serve as a conceptual foundation for Islamic educational reform that remains ethically grounded while responsive to contemporary challenges. This research employs a qualitative descriptive approach using historical, philosophical, and phenomenological methods. Data were collected through field observations and in-depth interviews at Pondok Pesantren Darun Nahdlatain NW Pancor and Pondok Pesantren Syaikh Zainuddin NW Anjani, as well as document analysis of primary texts, particularly Wasiat Renungan Masa Pengalaman Baru, complemented by relevant secondary literature on pesantren modernization and the Society 5.0 paradigm. The findings indicate that Maulana Syaikh’s educational vision integrates ta'lim (instruction), tarbiyah (character formation), and ta'dib (ethical cultivation) into a holistic model that harmonizes knowledge ('ilm) and righteous action ('amal). His emphasis on tawhid and tazkiyah al-nafs as moral foundations aligns with the human-centered learning orientation promoted in Society 5.0, which prioritizes ethical digital literacy, creativity, and social empowerment. The study concludes that pesantren modernization inspired by Maulana Syaikh’s thought is not a departure from Islamic tradition but a dynamic synthesis between spiritual values and technological innovation, offering a transformative framework for nurturing morally grounded, socially responsible, and future-ready Muslim learners.